2001
DOI: 10.1021/ic010615c
|View full text |Cite
|
Sign up to set email alerts
|

Three-Coordinate Copper(II)−Phenolate Complexes

Abstract: The reactions of LCuCl (L = 2,4-bis((2,6-diisopropylphenyl)imido)pentane (L(iPr)), 2,4-bis((2,6-diisopropylphenyl)imido)-3-chloropentane (L(CliPr))) with the phenolates TlOAr (Ar = C(6)H(3)Me(2), C(6)H(4)OMe, C(6)H(4)tBu) and NaOC(6)H(3)(tBu)(2) were explored. Novel three-coordinate Cu(II)-phenolates, LCuOAr, were isolated from the reactions with the thallium phenolates and were characterized by X-ray crystallography and spectroscopy (UV-vis, EPR). The complexes feature short Cu-O(phenolate) distances (average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
115
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 26 publications
11
115
1
1
Order By: Relevance
“…The UV absorption bands observed at 385, 388 and 395 nm for complexes 1, 2 and 3, respectively can be attributed to the ligand to Cu(II) charge transfer transition (LMCT) [26,27]. Those very weak low-intensity absorption bands associated with d − d transitions at 670, 675 and 676 nm may be assigned for to a Cu(II) d-d transition [26][27][28][29] for 1, 2 and 3, respectively and support the five-coordinated geometry around copper(II) ions with the CuN 4 chromophoric group.…”
Section: Uv/vis Spectramentioning
confidence: 94%
“…The UV absorption bands observed at 385, 388 and 395 nm for complexes 1, 2 and 3, respectively can be attributed to the ligand to Cu(II) charge transfer transition (LMCT) [26,27]. Those very weak low-intensity absorption bands associated with d − d transitions at 670, 675 and 676 nm may be assigned for to a Cu(II) d-d transition [26][27][28][29] for 1, 2 and 3, respectively and support the five-coordinated geometry around copper(II) ions with the CuN 4 chromophoric group.…”
Section: Uv/vis Spectramentioning
confidence: 94%
“…28 Other β-diketiminates with smaller arene and/or backbone substituents yield chloride-bridged dimeric structures, [LCu(μ-Cl)] 2 , in the solid state. 29 The thioether sulfur atom is bound to the Cu(II) center in both complexes, with a Cu-S bond distance of 2.3793(11) Å in Me 2 L iPr,SMe CuCl and 2.5941(9) Å in Me 2 L iPr,SPh CuCl, which contains the more bulky phenyl group on the thioether arm. These Cu(II)-thioether bond distances fall within the range of such distances reported previously (2.28-2.91 Å, avg.…”
Section: Synthesis and Characterization Of Cu(ii) Complexesmentioning
confidence: 99%
“…In contrast, Tolman et al recently reported the preparation of a copper(I) compound with the β-diketoiminate ligand in which the copper formed a six-membered CuN 2 C 3 ring. [35] A possible explanation for this different behaviour might be that the soft Cu I prefers coordination with the soft carbon atom while the harder Cu II prefers coordination with the harder nitrogen atoms. The CuϪC bond length of 2.089(6) Å is similar to those found in the literature.…”
Section: Molecular Structuresmentioning
confidence: 99%